International co-ordination of e-commerce - Stefan Mai (Universität zu Köln, Institut für Wirtschaftspolitik (iwp), 2002)
Despite the world-wide stock market breakdown of the internet economy in the year 2001, the new information and communication technologies will enable firms to integrate world-wide e-commerce in their business. This will facilitate the entry of firms in every connected country into international markets and perhaps value up their market position. Therefore, the world-wide use of information and communications technology, in particular e-commerce is fostered. To attain this, there are lot of attempts to regulate the e-economy on an international level as there are uncertainties in legal certainty, data protection or the digital divide between industrialised and development countries. The paper addresses this topic and shows which playing fields of co-ordination in ecommerce are relevant in general and how they are recently implemented in international co-ordination activities by various organisations and states e.g., the European Union, the United States or the WTO.
Keywords: F42; 330; E-Business; Internet; Regulierung; International; Internationale wirtschaftspolitische Koordination; Welt